Diphenyl diselenide modulates splenic purinergic signaling in silver catfish fed diets contaminated with fumonisin B1: An attempt to improve immune and hemostatic responses - Baldissera M.D. (2020)
© 2019 Elsevier Inc.The aim of this study was to determine whether purinergic signaling is a pathway associated with fumonisin B1 (FB1)-induced impairment of immune and hemostatic responses. We also determined whether dietary supplementation with diphenyl diselenide (Ph2Se2) prevents or reduces these effects. Splenic nucleoside triphosphate diphosphohydrolase (NTPDase) activity for adenosine triphosphate (ATP) and adenosine diphosphate (ADP) as substrates and total blood thrombocytes counts were significant lower in silver catfish fed with FB1-contaminated diets than in fish fed with a basal diet, while splenic adenosine deaminase (ADA) activity and metabolites of nitric oxide (NOx) levels were significant higher. Also, glutathione peroxidase (GPx) and superoxide dismutase (SOD) activities were significant lower in silver catfish fed with FB1-contaminated diets than in fish fed with a basal diet. Dietary supplementation with 3 mg Ph2Se2/kg of feed effectively modulated splenic NTPDase (ATP as substrate), ADA, GPx and SOD activities, as well as NOx levels, and was partially effective in the modulation of spleen NTPDase activity (ADP as substrate) and total blood thrombocytes count. These data suggest that splenic purinergic signaling of silver catfish fed with FB1-contaminated diets generates a pro-inflammatory profile that contributes to impairment of immune and inflammatory responses, via reduction of splenic ATP hydrolysis followed possible ATP accumulation in the extracellular environment. Reduction of ADP hydrolysis associated with possible accumulation in the extracellular environment can be a pathophysiological response that restricts the hemorrhagic process elicited by FB1 intoxication. Supplementation with Ph2Se2 effectively modulated splenic enzymes associated with control of extracellular nucleotides (except ADP; that was partially modulated) and nucleosides, thereby limiting inflammatory and hemorrhagic processes.